Hamstring strength and morphology progression after return to sport from injury - Sanfilippo, J. L.; Silder, A.; Sherry, M. A.; Tuite, M. J. (Medicine & Science in Sports & Exercise, 2013)
Purpose: Hamstring strain reinjury rates can reach 30% within the initial 2 wk after return to sport (RTS). Incomplete recovery of strength may be a contributing factor. However, relative strength of the injured and unaffected limbs at RTS is currently unknown.